Association between Slip Severity and Muscle Synergies of Slipping - Nazifi, Mohammad Moein; Beschorner, Kurt E.; Hur, Pilwon (Frontiers in Human Neuroscience, 2017)
Falls impose significant negative impacts to the US population and economy. A significant number of falls may be prevented via appropriate slip-responses since a strong relation exists between slips and falls. More importantly, as severe slips are more prone to result in a fall, identifying severe slippers along with the responsible factors for their adverse motor control and severe slipping should be the highest priority in fall prevention process. Previous studies have suggested that muscle synergies may be building blocks of the central nervous system in controlling motor tasks. Muscle synergies observed during slipping (‘post-slip-initiation synergies ‘or just briefly, ‘slipping muscle synergies’), may represent the fundamental blocks of the neural control during slipping. Hence, studying the differences in slipping muscle synergies of mild and severe slippers can potentially reveal the differences in their neural control and subsequently, indicate the responsible factors for the adverse post-slip response in severe slippers. Even though the slipping muscle synergies have been investigated before, it still remains unclear on how the slip severity is associated with the slipping muscle synergies. More importantly, muscle synergies can be interpreted not only as neural blocks but also as physical sub-tasks of the main motor task. Hence, studying the differences of slipping synergies of mild and severe slippers would reveal the discrepancies in sub-tasks of their post-slip response. These discrepancies help pinpoint the malfunctioning sub-function associated with inadequate motor response seen in severe slippers. Twenty healthy subjects were recruited and underwent an unexpected slip (to extract their slipping synergies). Subjects were classified into mild and severe slippers based on their Peak Heel Speed (PHS). An independent t-test revealed several significant inter-group differences for muscle synergies of mild and severe slippers indicating differences in their neural control of slipping. A forward dynamic simulation was utilized to reveal the functionality of each synergy. Decomposition of slipping into sub-tasks (synergies), and finding the malfunctioning sub-task in severe slippers is important as it results in a novel targeted motor-rehabilitation technique that only aims to re-establish the impaired sub-task responsible for the adverse motor-response in severe slippers.